Longitudinal Evaluation of Gingival Margin Modifications During Treatment with Clear Aligners: A Retrospective Clinical Study in Growing Patients - Marco Clementini; Chiara Pavoni; Francesca Gazzani; Francesca Chiara De Razza; Letizia Lugli; Arianna Malara; Paola Cozza; Roberta Lione (Applied Sciences, 2026)
Background: The aim of this study was to evaluate gingival margin modifications during and after orthodontic treatment with Clear Aligners in paediatric patients. Secondary objectives included assessing the relationship between gingival changes and different types of tooth movement and evaluating the stability of these changes after treatment completion. Methods: A total of 50 patients (26 f, 24 m, mean age: 7.6 ± 1.1 years) in mixed dentition were enrolled. Inclusion criteria were good general health, plaque and gingival indices below 20%, good compliance with aligners, and no prior orthodontic treatment. Patients with periodontal issues, medications influencing gingival response, or with poor expected compliance were excluded. Patients were treated using Clear Aligners and attachments to facilitate specific tooth movements (expansion, intrusion, and rotational corrections). Measurements were performed at four time points: before treatment (T0), after 6 months (T1), at the end of treatment (T2), and 12 months post-treatment (T3). At each time point, intraoral scans, clinical photographs, and periodontal measurements were recorded. Results: A statistically significant increase in gingival margin height was observed from baseline to T1 (+0.29 mm), T2 (+0.44 mm), and T3 (+0.39 mm). Mean Changes between T0 and T3 were +0.39 ± 0.22 (p ≤ 0.001). A total of 60% of patients demonstrated a coronal migration of the gingival margin. Gingival Index showed a non-significant increase at T1, followed by normalization at T2 (p = 0.481) and T3 (p = 0.637). Plaque Index (PI) remained stable throughout the observation period. Expansion was associated with the greatest gingival change (+0.52 mm), followed by intrusion (+0.45 mm). Conclusions: Clear aligner treatment in mixed dentition appears to produce favourable and stable gingival margin modifications, with minimal adverse periodontal effects when properly monitored.